Simulasi Distribusi Tegangan dan Deformasi pada Sasis Truk Light Duty dengan Variasi Panjang Rangka Sisi Menggunakan Metode Elemen Hingga - Ethys Pranoto; Gunawan Gunawan; Rifano Rifano; Ery Muthoriq; Siti Shofiah (Jurnal Teknik Terapan, 2026)
: In the field of freight transportation, changes to vehicle structures, particularly in the chassis length dimension, are commonly carried out to increase load-carrying capacity. One form of such change involves extending the frame length and adjusting the wheelbase in commercial vehicles with a 1.2 axle configuration. Although this approach can increase the volume of cargo that can be transported, alterations in structural dimensions have the potential to affect the load distribution contour on the vehicle frame. An uneven load distribution may lead to increased stress in certain areas, greater deformation, and a reduction in the structural safety level, which can ultimately affect the reliability and operational safety of the vehicle. This study aims to examine the effect of chassis length variations on the characteristics of the load distribution contour in freight transport vehicles with a 1.2 axle configuration. The analysis focuses on evaluating changes in stress, deformation, and the safety factor of the frame structure resulting from variations in chassis length and wheelbase adjustments. The approach used is a numerical simulation based on the Finite Element Method, utilizing software to model and evaluate the structural response of the chassis frame under loading conditions. The simulation results show that an extension of the chassis length, accompanied by changes in wheelbase position, leads to higher displacement and stress distribution in the chassis frame. The extension of the chassis side frame structure leads to an increase in stress values, which even exceed the material’s yield strength, with a maximum value reaching approximately 3709 MPa. In addition, the displacement reaches up to 81 mm, indicating increased frame deflection. Therefore, any changes in chassis dimensions must be designed by carefully considering load distribution and overall structural strength in order to maintain the reliability and safety of freight vehicles.